2007
DOI: 10.1371/journal.pcbi.0030108
|View full text |Cite
|
Sign up to set email alerts
|

A Mass Conserved Reaction–Diffusion System Captures Properties of Cell Polarity

Abstract: Cell polarity is a general cellular process that can be seen in various cell types such as migrating neutrophils and Dictyostelium cells. The Rho small GTP(guanosine 5′-tri phosphate)ases have been shown to regulate cell polarity; however, its mechanism of emergence has yet to be clarified. We first developed a reaction–diffusion model of the Rho GTPases, which exhibits switch-like reversible response to a gradient of extracellular signals, exclusive accumulation of Cdc42 and Rac, or RhoA at the maximal or min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
190
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(216 citation statements)
references
References 58 publications
9
190
0
Order By: Relevance
“…In the bistable region, we have two stable states: the anterior-domain state with low ½P m and the posterior-domain state with high ½P m . The property of the bistability with mass conservation can form AP polarity in our model, as the previous studies (Mori et al, 2008;Otsuji et al, 2007;Trong et al, 2014).…”
Section: Formation Of Ap Polarity Pattern By Self-recruitment Mechanismsupporting
confidence: 72%
See 1 more Smart Citation
“…In the bistable region, we have two stable states: the anterior-domain state with low ½P m and the posterior-domain state with high ½P m . The property of the bistability with mass conservation can form AP polarity in our model, as the previous studies (Mori et al, 2008;Otsuji et al, 2007;Trong et al, 2014).…”
Section: Formation Of Ap Polarity Pattern By Self-recruitment Mechanismsupporting
confidence: 72%
“…Dawes and Munro (2011) also has shown that cortical flow is not required for the establishment of the AP polarity pattern, but a bistable switch mechanism of PAR proteins are important. Mori et al (2008) and Otsuji et al (2007) have suggested the mathematical structure for cell polarity patten, and showed that the mass-conservation and the bistability in chemical reaction are sufficient, in the absence of the advective transport. Tostevin and Howard (2008) have considered the formation of the anterior-posterior polarity pattern using a model combined with the effect of actomyosin contraction which directly influences a biochemical reaction of polarity proteins, but the effect of advective transport was not supposed into the model.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, a similar phenomenon occurs in some computational models of positive feedback by local activation (Goryachev & Pokhilko 2008, Otsuji et al 2007). This suggests that both the growth of clusters and their winnowing down to yield a single cluster might be intrinsic to this positive feedback mechanism.…”
Section: Number and Size Of Polarity Sitessupporting
confidence: 67%
“…52 This model belongs to a class of mass-conserved reaction-diffusion models where negative regulation of a component in a reaction system can be traced back to its limited supply. 53 We propose that the regulation of spatiotemporal dynamics of Rac1 activity is governed by a similar mechanism (Fig. 3B).…”
Section: Acknowledgmentsmentioning
confidence: 80%